Peran Badan Kepegawaian Pengembangan Sumberdaya Manusia (BPSDM) terhadap Kinerja Pegawai Negeri Sipil - Tanthawi Ishak; Muhammad Muhammad; Nurmayana Nurmayana (Sekolah Tinggi Ilmu Administrasi Nasional, 2020)
The Human Resources Development Personnel Agency (BKPSDM) performs an important role in improving the performance of qualified employees through education and training programs that are prepared to answer the needs of public demands. The benefits of training for employees are not only for BKPSDM work productivity but also for ASN personnel after gaining training experience both in the transfer of knowledge, behavior, attitudes, and career duties. The obstacles faced by the BKPSDM of Lhokseumawe City are basically external obstacles, namely the reduction of irrelevant budgets as proposed to carry out the BKPSDM program and the unavailability of building facilities such as halls in carrying out education and training for employees within the local government. Meanwhile, internal obstacles have so far not been found and have not become the main problem to be criticized. Basically, BKPSDM Lhokseumawe City has the task of implementing administrative affairs, compiling annual, medium-term, and long-term work programs. In addition, he is also responsible for the formulation of technical personnel policies, the implementation of education and training for civil servants, as well as administrative services for the smooth implementation of education and training.